Analisis Kompetensi Digital SDM pada Pelaku Fashion Kreatif dalam Meningkatkan Penjualan Online - Arfinah; Meisya Rusdiana Putri; Kiana Amanda Salsabilah (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
Digital advancements have brought significant transformations across various economic sectors, including the creative economy sector that is continuously growing in Indonesia. One segment of this sector greatly impacted by digital progress is the creative fashion subsector. The emergence of digital platforms such as social media and marketplaces has shifted the marketing and sales of fashion products from traditional systems to online-based models. This shift requires business operators in the creative fashion field to employ a workforce that excels not only in creativity and product innovation but also possesses sufficient digital skills to compete in an increasingly competitive digital market. However, in reality, many creative fashion operators still face various challenges in utilizing digital technology. These challenges include low digital capabilities among workers, difficulties in managing social media and marketplaces, a lack of ideas for creating promotional digital content, and a poor understanding of effective online marketing strategies. These digital limitations result in suboptimal online marketing activities, ultimately impacting low online sales for creative fashion business operators. This study aims to empirically analyze the influence of workforce digital capabilities on increasing online sales among creative fashion industry operators. The study employs a quantitative method by distributing questionnaires to creative fashion entrepreneurs who have already used social media and marketplaces for promotion and product sales. Workforce digital capabilities are measured through aspects such as proficiency in using digital technology, expertise in leveraging social media, creativity in producing digital content, and the ability to communicate and interact with customers online. Meanwhile, online sales are assessed based on indicators including the quantity of goods sold, sales revenue, and the growth rate of online sales. The study reveals that workers' digital capabilities have a positive and significant influence on increasing online sales for creative fashion industry operators. The findings indicate that the higher the workers' digital capabilities, the more effective their online marketing strategies, thereby boosting the sales results of creative fashion products. The hope from this study is to provide contributions to the theory regarding workforce digital capabilities and digital marketing, as well as to assist creative fashion business operators, the government, and other relevant parties in formulating human resource development strategies aimed at enhancing business competitiveness in the digital era.